Implementation of the “Merdeka Belajar–Kampus Merdeka” Policy at Sunan Gunung Djati State Islamic University Bandung - Reza Noprial Lubis; Rizki Akmalia; Amiruddin Siahaan (JTP - Jurnal Teknologi Pendidikan, 2025)
This study seeks to identify how the Independent Learning–Independent Campus (MBKM) policy is implemented at Sunan Gunung Djati State Islamic University Bandung. The research employs a descriptive qualitative method, with data collection techniques consisting of observation, interviews, and documentation. Data analysis follows the steps of data reduction, data presentation, and drawing conclusions. This study is divided into six stages, namely: pre-research, formulation of research focus and questions, development of instruments, data collection and interviews, data analysis, and presentation of research results in the form of a research report. Through this study, it is expected that the MBKM policy at Sunan Gunung Djati State Islamic University Bandung will enhance students’ innovation, creativity, capacity, motivation, and independence in seeking and generating knowledge based on real-world conditions and environmental dynamics. In addition, this research is expected to provide added value for partner institutions—particularly Sunan Gunung Djati State Islamic University Bandung—by presenting an in-depth analysis of the best ways to integrate national policies with local and religious needs within the institution